Belt and Road Initiative dan Refleksi Budaya China Kuno - Nugraha, Arif; Sinaga, Obsatar; Dermawan, Windy (Padjadjaran Journal of International Relations, 2024)
Artikel ini menganalisis pengaruh budaya China Kuno terhadap kepentingan nasional China melalui Belt and Road Initiatives. Pemerintah China mencoba untuk menghidupkan kembali kejayaan China Kuno dalam memanfaatkan jalur perdagangan yang terletak pada Jalur Sutra Kuno melalui kerangka BRI. Artikel ini akan menggunakan konsep budaya dalam konteks hubungan internasional dan konsep kepentingan nasional. Penelitian ini akan menggunakan metode kualitatif dengan mengumpulkan informasi, seperti dokumen, buku, sumber dari internet dan catatan. Penulis menemukan korelasi antara budaya China Kuno yaitu Jalur Sutra Kuno dengan inisiasi China melalui kerangka Belt and Road Initiatives. Pemerintah China menggunakan sejarah dan budaya China Kuno, khususnya Jalur Sutra Kuno sebagai landasan mereka untuk membuat sebuah kebijakan. China ingin mengembalikan kejayaan masa lampau ke masa kini, tentunya dengan berbagai adaptasi karena perubahan zaman.This article analyzes the influence of Ancient Chinese culture on China's national interests through the Belt and Road Initiatives. The Chinese government is trying to revive the glory of Ancient China by utilizing trade routes that lie on the Ancient Silk Road through the framework of the BRI. This article will use the concept of culture in the context of international relations and the idea of national interest. This study will use qualitative methods by collecting information, such as documents, books, sources from the internet, and notes. The author found a correlation between the culture of Ancient China, namely the Ancient Silk Road, and Chinese initiation through the framework of the Belt and Road Initiatives. The Chinese government uses the history and culture of Ancient China, especially the Ancient Silk Road, as their basis for making policies. China wants to return the glory of the past to the present, with various adaptations due to changing times.